Bibliometric analysis of scientific production in small-sided games - Filipe Manuel Clemente (Termedia Publishing House, 2023)
Purpose The present study constitutes a comprehensive bibliometric analysis aimed at evaluating both the quantity and quality of scientific output pertaining to small-sided games (SSGs). This analysis employs science mapping techniques to explore networks and clusters within publications, authors, and keywords associated with the SSG field. Methods The process of identifying relevant studies involved a rigorous search across reputable databases, including PubMed, Scopus, and Web of Science (Core Collection). Inclusion criteria stipulated that studies must primarily focus on SSGs, with explicit references to SSGs or synonymous terms in the title or abstract. Results Out of 3,125 initially retrieved titles, 1,084 met these criteria and were included. When considering five-year intervals, the average number of annual publications from 2019 to 2023 stood at 122.2. It is noteworthy that, in the last five years (2019-2023), a total of 34 reviews were published. Additionally, there is an increasing prevalence of keywords related to soccer, athletic performance, global positioning systems and their associated metrics, as well as terms associated with tactical behaviour, validity, and reliability. Conclusions The bibliometric analysis revealed that the majority of studies in this field have predominantly focused on training load monitoring, particularly concerning acute effects and with a strong emphasis on soccer. Future research directions should aim to address existing imbalances, including the incorporation of more experimental randomised controlled studies, a broader range of sports, and the inclusion of female participants. Additionally, mixed-methodological approaches should be encouraged to enhance the depth and breadth of the field.